Teaching Speaking As A Productive Skill - Hasibuan, Kalayo (Journal of English and Arabic Language Teaching, 2012)
The term of productive skills according to Harmer (2007) is the language skills where the students produce the language themselves. The language language skills that are categorized into productive skills are speaking and writing. While, reading and listening are as receptive skills.Both components of skills depict  how language as means of communication works. These skill components are messages delivered through spoken and printed texts that are produced by language learners.  The messages produced by students in spoken form are categorized as speaking; while the messages produced by students through written form are writing. Both skills are prescribed in the following chart.